Customer-Centricity in Organized Retailing A Guide to the Basis of Winning Strategies - Dash, Manoj Kumar; Sahu, Manash Kumar; Bhattacharyya, Jishnu; Sakshi, Shivam (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book provides a compendium of cutting-edge knowledge for an efficacious retailing strategy, with lessons from the organized retailing sector in India. It explores customer needs and their impact on developing successful retailing strategies and organized retailing in emerging economies with changing consumer behavior. It discusses the importance of developing appropriate retailing strategies in the context of an emerging economy, being agile and forward-thinking to implement a customer-centric approach across the retail value chain's upstream and downstream actions, and the requirement of clarity on the exact tools and techniques that will allow the retailers to move from their present product-centric state to the looked-for customer-centric state. This book aids the practitioners in developing and adopting a culture of customer-centricity and focuses on various retail strategy concepts and their implementation. It aims to present the multifaceted and multifarious questions of retail marketing in two studies, where each study provides a comprehensive solution. Dr. Manoj Kumar Dash is a faculty at ABV-Indian Institute of Information Technology and Management Gwalior, India. He specializes in multivariate analysis, econometrics, and multi-criteria optimization. His research work appears in International Journal of Production Research, Journal of Environmental Management, and Online Information Review. He has won several best paper awards. Dr. Manash Kumar Sahu is an Assistant Professor at ASBM University in Bhubaneshwar, Odisha. His research interests include consumer behavior in retailing, customer relationship management, and digital & social media marketing. He won the Best Research Scholar Award at Berhampur University. Jishnu Bhattacharyya is a Ph.D. Candidate in marketing at the University of Nottingham. He has previously worked as a Project Scientist for IIT Delhi. His research interests include sustainability communication, socially responsible consumption, consumer interactions with technology, and service robots. His work has appeared in academic journals, and he has also co-edited books, co-authored a book, and written case studies. Dr. Shivam Sakshi is a Postdoctoral Associate at the Indian Institute of Management Bangalore. He holds a Ph.D. from the University of Debrecen, Hungary. He has previously worked as Senior Project Training Manager at the National Institute of Rural Development and Panchayati Raj, Hyderabad. His research interests include consumer analytics, retail management, consumption behavior, virtual markets, and rural markets.
Introduction -- Customer Centricity -- Organized Retailing -- Tool 1: Structural Equation Modelling (SEM) -- Customer Segmentation -- Tool 2: Multiple Criteria Decision Analysis (MCDA) -- Strategic Mismatch -- Developing an Appropriate Strategy -- Discussion.
Keywords: Marketing; Business; Management science; Business -- Data processing; Retail trade; Marketing; Business and Management; Business Analytics; Trade and Retail